Preclinical evaluation of antigen-specific B-cell depletion for phospholipase A2 receptor membranous nephropathy with chimeric autoantibody receptor T cells - Altun, Burcin; Zhao, Gexin; Wang, Baomei; Mao, Xuming; Manfredo-Vieira, Silvio; Willis, Elinor; Radaelli, Enrico; Goodman, Emma E; Boesteanu, Alina C; Gill, Saar I; Patel, Darshil R; Wong, Steven; et al. (Kidney international, 2025)
Phospholipase A2 receptor (PLA2R)-associated membranous nephropathy (MN) is a leading cause of nephrotic syndrome in adults, driven by autoantibodies that target PLA2R on kidney podocytes. Antibody-based therapy with rituximab induces broad B-cell depletion but is associated with risks of serious infection and reduced efficacy in patients with high proteinuria. Here, we determined the feasibility of developing chimeric autoantibody receptor T-cell (CAART) therapy for PLA2R-specific B-cell depletion in PLA2R MN. PLA2R-CAART was produced by T-cell lentiviral transduction. In vitro cytotoxicity and specificity were evaluated against B-cell lines targeting PLA2R immunodominant epitopes and primary PLA2R MN B cells. Adsorption of PLA2R MN IgG was evaluated to determine the extent of pathogenic autoantibody targeting by candidate PLA2R-CAART designs. Specific cytotoxicity, engraftment capability, and off-target toxicity were evaluated in a xenografted anti-PLA2R Nalm-6 preclinical mouse model, with additional toxicology screening by human membrane proteome arrays. We engineered CAARTs targeting key PLA2R epitopes to selectively deplete autoreactive B cells. C17- and C178-CAART (encompassing CysR, CTLD1, and CTLD7, with/without CTLD8 domains) were successfully expressed on primary T cells and demonstrated specific in vitro cytotoxicity against anti-PLA2R B-cell lines targeting CysR, CTLD1, and CTLD7 epitopes. In co-incubation assays with primary B cells or plasma from patients with MN, C17- and C178-CAART significantly reduced anti-PLA2R B cells and adsorbed 69-97% of plasma anti-PLA2R antibody reactivity. In vivo, C17- and C178-CAART treatment in the Nalm-6 xenograft model resulted in significant reduction in target cell outgrowth with C17-CAART showing slight but consistently increased cytotoxic activity. Specificity testing through comprehensive in vivo pathologic analysis and a high-throughput membrane proteome array analysis showed no significant off-target binding for either C17- or C178-CAART. Our findings establish preclinical proof-of-concept for the therapeutic potential of antigen-specific B-cell depletion by PLA2R-CAART. Additional studies are required to determine clinical feasibility of PLA2R-CAART for PLA2R MN therapy.